2004
DOI: 10.1097/01.aud.0000120365.97792.2f
|View full text |Cite
|
Sign up to set email alerts
|

Music Perception with Temporal Cues in Acoustic and Electric Hearing

Abstract: Cochlear-implant listeners performed normally in tempo discrimination, but significantly poorer than normal-hearing listeners in rhythmic pattern identification and melody recognition. While both temporal (rhythmic) and spectral (pitch) cues contribute to melody recognition, cochlear-implant listeners mostly relied on the rhythmic cues for melody recognition. Without the rhythmic cues, high spectral resolution with as many as 32 bands was needed for melody recognition for normal-hearing listeners. This result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
311
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(344 citation statements)
references
References 38 publications
(62 reference statements)
23
311
2
8
Order By: Relevance
“…Of course, many other factors can contribute to CI users' melodic pitch perception (e.g., acoustic frequency allocation, electrode location, pattern of nerve survival, experience, etc.). The number of spectral channels has been shown to limit CI performance in difficult listening situations (Friesen et al, 2001;Kong et al, 2004;Luo et al, 2007). Data from the present study and from Fu and Nogaki (2005) suggest that channel interaction may also limit CI performance where perception of pitch cues may be beneficial.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Of course, many other factors can contribute to CI users' melodic pitch perception (e.g., acoustic frequency allocation, electrode location, pattern of nerve survival, experience, etc.). The number of spectral channels has been shown to limit CI performance in difficult listening situations (Friesen et al, 2001;Kong et al, 2004;Luo et al, 2007). Data from the present study and from Fu and Nogaki (2005) suggest that channel interaction may also limit CI performance where perception of pitch cues may be beneficial.…”
Section: Discussionmentioning
confidence: 52%
“…Kong et al (2004) observed that decreasing the number of spectral channels influenced melody recognition. Less is known about the effects of channel interaction on music perception, specifically melodic pitch perception.…”
Section: Introductionmentioning
confidence: 99%
“…While implant listeners generally are quite good at perceiving the rhythmic cues in music (Gfeller et al, 1998;Kong et al, 2004;McDermott, 2004), their recognition of melodies is usually much poorer than normal, especially when the rhythmic or lyrical cues are not available (Gantz et al, 2005;Kong et al 2004;Gfeller et al, 2002). The residual low-frequency acoustic hearing of A+E patients can provide assistance in pitch perception in these patients.…”
Section: A+e Results For Musicmentioning
confidence: 99%
“…Certainly listening to music is one situation where implant listeners have been shown to have severe perceptual deficits (e.g. Gfeller et al, 2002;Kong et al, 2004). For example in Gfeller et al (2002), while normalhearing listeners had no difficulty in discriminating piano notes one semitone apart (adjacent piano keys, approximately 6% frequency difference), implant listeners' ability to discriminate pitches was generally much poorer, the typical threshold was 1/2 octave (6 semitones), with some listeners requiring as much as 2 octaves difference between notes for discrimination.…”
Section: Shortcomings Of Electrical Stimulationmentioning
confidence: 99%
“…Sound can be separated into temporal envelope and fine structure components. The temporal envelope consists of amplitude information and plays an important role in speech intelligibility, whereas fine structure corresponds to spectral cues and is more heavily utilized during perception of pitch, music, and sound localization 11, 29, 30, 31. Unfortunately, fine structure processing (FSP) has not been incorporated into the majority of current processing strategies.…”
Section: Introductionmentioning
confidence: 99%